(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to know the prevalence of marital compatibility among married female students at Tishreen University, and know the differences in marital compatibility according to some variables (method of marriage, place of residence, presence of children). The research was applied to a sample of married students at Tishreen University, whose number was (100) students. To achieve this goal, the marital compatibility scale prepared by (Ammar, 2015) was used, which includes dimensions (intellectual, affectionalemotional, sexual, and social compatibility) distributed within (54) items. The researcher conducted the psychometric study of the scale to ensure its validity and reliability in relation to the current research sample is high, and there are no statistically significant differences in the marital compatibility of the research sample according to the variable of the place of residence and the presence of children. As for the variable of the method of marriage it was found that there were statistically significant differences in favor of marriage after a love story.